The Determinants of Relative Price Variability: Further Evidence from Argentina - Caraballo, María Angeles (2008)
This paper analyses the relative price variability (here after, RPVI) for Argentina from 1960 to 1993. We have distinguished a first period (1960-1975) with a moderate and stable inflation and a second one (1975-1993) with four inflation regimes: moderate, high, very high and hyperinflation. Results show that for the high, very high, and hyperinflation regimes, volatility and all components of inflation are relevant in explaining RPVI; but for the moderate regime, volatility and uncertainty are insignificant, and the impact of expected and unexpected inflation shocks depends on whether inflation is stable or not.